Assessment of aflatoxin B1 in maize and awareness of aflatoxins in Son La, Vietnam - Xuan Thi Thanh Nguyen; Thuy Thi Thanh Nguyen; Hung Nguyen-Viet; Khanh Ngoc Tran; Lindahl, Johanna F.; Grace, Delia; Thanh Minh Ha; Hu Suk Lee (Informa UK Limited, 2018)
Aflatoxin B1 (AFB1) is a fungal by-product which causes acute and chronic toxicity in humans and many other animals. This research was conducted to evaluate the prevalence of AFB1 contamination in maize and residents’ awareness of aflatoxins in Son La province, Vietnam. Maize samples were randomly collected from Son La province using multi-stage sampling. We used cut-off levels of 5 and 20 μg/kg and calculated the mean, median and range for each district. In addition, a questionnaire collected information from households about their knowledge, attitude and practice related to moldy maize. Out of 378 maize samples from Son La, 204 (54.0%) and 141 (37.3%) were contaminated with AFB1 at more than 5 µg/kg and 20 µg/kg, respectively. Mai Son district had the highest proportion of samples (54.0%) using a cut-off level > 20 µg/kg, and Yen Chau district the lowest (4%). People from the Thai ethnic group were 30.9 times more likely to consume meat from animals fed moldy maize than people from the Kinh ethnic group (p = 0.003). Maize in Son La is contaminated with AFB1 at levels which imply better control of aflatoxins in maize for human consumptions and animal feed is needed.